DIAGNOSTIC ANALYSIS OF THE RELEVANCE OF DOING BUSINESS BY YOUNG ENTREPRENEURS IN THE POST-PANDEMIC COVID-19 PERIOD - Zhosan, Hanna; Khoroshko, Anna (Таврійський науковий вісник. Серія: Економіка, 2022)
The article highlights a marketing study of the preconditions for starting a business by young entrepreneurs by polling existing and potential entrepreneurs under the age of 35 on social networks. The problems of the development of existing enterprises during the introduction of quarantine restrictions due to coronavirus (COVID-19) are considered. Obstacles at the beginning of starting a business by young entrepreneurs and their willingness to adapt to coronavirus quarantine restrictions are analyzed (COVID-19). One in two young entrepreneurs is found to be partially affected by quarantine restrictions due to the coronavirus epidemic (COVID-19), and the rest of the self-employed people responded that the business is fully operational. Among the difficulties that arose during the quarantine, there was a decrease in social activity and limited visits to customers, reduced activity in those areas on which their business depended, lack of demand and orders. It is established that one of the important aspects is the focus on creating conditions to support young entrepreneurs and the necessary guarantees of their activities, the competence of the state in matters of lending and preferential tax conditions for start-up entrepreneurs. It is also possible to consider exchange and training on the basis of universities in countries with high economic performance in comparison with Ukraine (for potential entrepreneurs), and government support programs for existing enterprises.